Scrutinizing global banking fragility: are larger or smaller banks more fragile? / Nur Hazimah Amran, Wahida Ahmad and Amir Alfatakh Yusuf - Amran, Nur Hazimah; Ahmad, Wahida; Yusuf, Amir Alfatakh (UiTM Press, 2024)
The study focuses on the funding fragility arising from the nature of the banking business due to asset-liability mismatches. Incorporating seven (7) countries with dual banking systems, the study aims to assess the global funding fragility of Islamic and conventional banks. The study employs a random effect model with a robust standard error that spans the period from 2009 to 2018, made up of 10-year unbalanced panel data. Islamic and conventional banks should be more cost-efficient and earn greater profitability to reduce funding fragility. Banks with wider income diversification and a higher capital level have a better advantage in lessening funding fragility. Banks that offer high financing growth are exposed to greater credit risk but empirically manage to control the funding fragility. The interaction effect reveals that larger conventional banks are less fragile than smaller conventional banks. On the contrary, larger Islamic banks are found to be more fragile than smaller Islamic banks.